Girty - Taylor, Richard, 1941- (Book collections on Project MUSE., 2020)
Along with Benedict Arnold, Simon Girty was one of the most hated men in early America. The son of an Irish immigrant, he was raised on the western Pennsylvania frontier but was captured by the Senecas as a teenager and lived among them for several years. This able frontiersman might be seen today as a defender of Native Americans, but in his own time he was branded as a traitor for siding with First Nations and the British during the Revolutionary War. He fought fiercely against Continental Army forces in the Ohio River Valley and was victorious in the bloody Battle of Blue Licks. In this classic work, Richard Taylor artfully assembles a collage of passages from diaries, travel accounts, and biographies to tell part of the notorious villain's story. Taylor uses the voice of Girty himself to unfold the rest of the narrative through a series of interior monologues, which take the form of both prose and poetry. Moments of torture and horrifying bloodshed stand starkly against passages celebrating beautiful landscapes and wildlife. Throughout, Taylor challenges perceptions of the man and the frontier, as well as notions of white settler innocence. Simon Girty's bloody exploits and legend made him hated and feared in Kentucky and the Ohio River Valley, but many who knew him respected him for his convictions, principles, and bravery. This evocative work brings to life a complex figure who must permanently dwell in the borderland between myth and fact, one foot in each domain.